2014
DOI: 10.1001/jama.2014.12716
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Imposition of a Maintenance of Certification Requirement and Ambulatory Care–Sensitive Hospitalizations and Health Care Costs

Abstract: Imposition of the MOC requirement was not associated with a difference in the increase in ACSHs but was associated with a small reduction in the growth differences of costs for a cohort of Medicare beneficiaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 26 publications
1
43
0
Order By: Relevance
“…(1) Hospitalizations for these conditions are understood as preventable, since the causes should be handled at a primary level of care. Therefore, these hospitalizations have been widely used as indicators of the impact of public policies and the accessibility and quality of basic health services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Hospitalizations for these conditions are understood as preventable, since the causes should be handled at a primary level of care. Therefore, these hospitalizations have been widely used as indicators of the impact of public policies and the accessibility and quality of basic health services.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these hospitalizations have been widely used as indicators of the impact of public policies and the accessibility and quality of basic health services. (1)(2)(3) In the field of child health, hospitalizations for ACSC indicate poor attention in primary care, especially since children are considered a priority due to their susceptibility to illness. (4) The importance of primary care for the prevention of hospitalizations is emphasized in several studies, such as one conducted in the United States, which concluded that children who were attended by ambulatory care teams with preventive actions and early detection of health problems had a significant reduction in hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…While lifelong learning for all physicians matters greatly, the added quality or value achieved through these requirements is unclear [28][29][30]. Regardless, bureaucratic requirements certainly generate considerable expense, paperwork, and, perhaps most egregious, loss of precious time [31].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown no difference in outcomes for patients cared for by internists with ABIM time-limited vs time-unlimited certifi cates across a panel of ten primary care performance measures [ 21 ], and no difference in ambulatory care-sensitive hospitalizations when comparing internists with ABIM time-unlimited and time-limited certifi cates [ 22 ], though there was a small reduction in the growth differences of costs for a cohort of Medicare benefi ciaries [ 22 ]. Diplomates of American Board of Family Medicine ( ABFM ) who completed Performance in Practice modules related to hypertension showed improvement in most quality measures evaluated; however, though most had chosen lipid control as their quality improvement focus, no improvement was seen for that particular measure [ 23 ].…”
Section: Is the Moc Program Performing As It Should?mentioning
confidence: 99%